Search for effective poverty reduction interventions by corporates in South Africa - Mogano, Reuben Mogato (My University, 2012)
Poverty remains a defining feature of the South African socio-economic landscape. The single most important issue facing South Africa 16 years after the transition to democracy is improving the lives of the rural and urban poor and promoting socio-economic opportunities for self-reliance. The current poverty reduction models and implementation strategies of the corporate sector do not impact significantly on the levels of poverty in South Africa. In other words, the contribution of corporate South Africa to poverty reduction is undermined by ineffective intervention models and implementation strategies. The research study purposely sampled the top 65 companies from the top 100 listed in Trialogue – an authoritative publication on corporate social investment. A total of twenty three (23) questionnaires were completed and returned by respondents. Five Executive Managers were randomly selected from the 65 companies for in-depth interviews. The purpose of this exercise was to solicit further views to enable substantive triangulation of data from other sources. The research study reveals that corporates in South Africa use different but complementary models and strategies in contributing towards poverty reduction. Education, particularly support for secondary school technology and science tuition, and early childhood development (ECD), constitute key interventions areas by corporates in poverty reduction. This is closely followed by support to Small Micro and Medium Enterprises (SMMES). There is no demonstrable evidence that Corporate Social Investment (CSI) is informed by a coherent theoretical framework in South Africa. Poverty reduction interventions are implemented in an unco-ordinated and fragmented manner resulting in limited impact on targeted communities. Some corporate decisions are based on what a company observes and believes in as opposed to a clearly iii defined and agreed strategy. CSI practitioners believe that corporates can improve the relevance of their current models and effectiveness of their implementation strategies in poverty alleviation through improved co-ordination, resource sharing, strategic partnership and collaboration as well as engaging closely with targeted communities. The current CSI models and strategies used by South African companies do not strategically leverage business-wide resources, opportunities and relationships to impact significantly on poverty levels in the country. In their current form, they are sub-optimal and unsustainable.
MBA thesis - WBS
Keywords: Corporate social investment; Poverty reduction